HUMAN TALENT: A SIGNIFICANT CONTRIBUTION TO ORGANIZATIONAL COMPETITIVENESS - Ortega-Galarza, Máximo; Pérez, Hólguer Rodrigo Altamirano; Rodas, Pablo Patricio Naranjo; Avilés, Moisés Nikolay Trujillo; Zarabia, Hugo Patricio Rosero; Coloma, Kathrina Samira Ortega; Coloma, Máximo Leonid Ortega; Pinzón, María Eugenia Tovar (Seven Editora, 2025)
The objective of the research was to analyze the connection between human talent and competitiveness in organizations, using a document-type methodology that arises from the review and analysis of scientific references to determine that, if an organization has achieved a performance above the competition, this favors the obtaining of opportunities in the market. This competitive advantage differentiates an organization from others and allows it to ensure that its strategic objectives can be met in the medium and long term. DOI: https://doi.org/10.56238/sevened2024.037-213